Omadacycline: A Newly Approved Antibacterial from the Class of Tetracyclines - Fernando Durães; Emília Sousa (Pharmaceuticals, 2019)
Omadacycline (Nuzyra®) is a new aminomethylcycline, approved by the U. S. Food and Drug Administration in 2018, as a tetracycline antibacterial. It can be used in community-acquired pneumonia and in acute bacterial skin and skin-structure infections. It was developed and is commercialized by Paratek Pharmaceuticals. It is a semisynthetic compound, derived from minocycline, capable of evading widely distributed efflux and target protection antibacterial resistance mechanisms and has demonstrated activity in a broad spectrum of bacteria.